Associations Between Mild Behavioral Impairment (MBI‐C) Affective Domains and Alzheimer's Disease Neuroimaging Biomarkers in Older Adults. (20th December 2022) - Mayblyum, Danielle V.; Quiroz, Yakeel T.; Langella, Stephanie; Udeogu, Onyinye J.; Jacobs, Heidi I.L.; Rubinstein, Zoe B.; Sperling, Reisa A.; Johnson, Keith A.; Blacker, Deborah; Marshall, Gad A; Gatchel, Jennifer R
Abstract: Background: Previous work has shown that neuropsychiatric symptoms (NPS) such as depression in older adults are associated with cognitive decline and brain pathology related to Alzheimer's disease (AD), but the constellation of NPS driving these associations is unclear. Traditionally, depressive symptoms have been assessed with the Geriatric Depression Scale (GDS), but newer NPS assessments, such as the Mild Behavioral Impairment‐Checklist (MBI‐C), have shown promise for identification of specific early features of symptomology. Here we examined the two affective domains of the MBI‐C in cognitively unimpaired older adults with moderate‐to‐severe depressive symptoms and non‐depressed older adults, and the association between these domains and neuroimaging biomarkers of AD. Method: 21 clinically normal (CN) older adults who met DSM5 criteria for major depression (MDD) (73.0±4.3 y.o., 62% female) and 25 non‐depressed older adults from related observational studies at our site (70.8±3.7 y.o., 64% female) underwent a clinical battery that included the GDS and MBI‐C self‐report domains focused on decreased interest‐motivation‐drive and increased dysphoria‐anhedonia‐anxiety (Range for each domain: 0–18). Participants completed neuroimaging consisting of MRI, amyloid‐(C 11 ‐PiB)‐PET, and tau‐(F 18 ‐FTP)‐PET. We focused analyses on neocortical amyloid and regional tau and atrophy in the amygdala and hippocampus. A Pearson correlation was used to assess the association between GDS total score and MBI‐C component scores. Linear regressions adjusted for age were used to investigate relationships between MBI‐C domains and ATN biomarkers. Result: GDS total score was correlated with both MBI‐C domains across all participants (Fig.1, p<0.01). In participants with MDD, the MBI‐C decreased interest‐motivation‐drive domain was associated with elevated FTP in the amygdala and hippocampus, while the increased dysphoria‐anhedonia‐anxiety domain was not significantly related to PET signal (Table 2, Fig.2). MBI‐C domains were not related to PET signal or atrophy in non‐depressed control participants. Conclusion: Preliminary findings with the MBI‐C suggest that the decreased interest‐motivation‐drive domain may be associated with tau pathology in older adults with moderate‐to‐severe depression. Additional work needs to be done in a larger depressed cohort to further understand the associations between specific depressive phenotypes and AD pathology.